2002
DOI: 10.1302/0301-620x.84b3.0840431
|View full text |Cite
|
Sign up to set email alerts
|

Calcifying Tendonitis of the Gastrocnemius

Abstract: We describe the clinical features of calcifying tendonitis in the medial head of gastrocnemius in three elderly female patients. The presenting symptom was chronic pain in the posteromedial area of the knee in two patients and acute pain in the back of the knee in one. All had limitation of movement of the knee and marked tenderness in the region of the tendinous origin of the medial head of gastrocnemius with posterior knee pain induced by stretching the tendon. An injection of 1% lidocaine and steroid into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Kernohan et al [12] mentioned a dolorous calcification of the lateral sesamoid bursa of the great toe. Iguchi et al [7] described the clinical features of calcifying tendinitis in the medial head of the gastrocnemius in three elderly female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Kernohan et al [12] mentioned a dolorous calcification of the lateral sesamoid bursa of the great toe. Iguchi et al [7] described the clinical features of calcifying tendinitis in the medial head of the gastrocnemius in three elderly female patients.…”
Section: Discussionmentioning
confidence: 99%
“…As the patient did not present with a clear history of trauma, the other differential diagnosis we should have considered is calcifying tendonitis of the gastrocnemius tendon. Iguchi et al 7 reported three cases of isolated non-traumatic calcifying tendonitis of the medial head of gastrocnemius tendon presenting with pain in the posterior medial aspect of the knee.…”
Section: Discussionmentioning
confidence: 99%
“…V literatuře se objevují kazuistiky výskytu depozit v různých lokalizacích, např. šlachy m.longus colli (17), m.gastrocnemius (18), m.pectoralis minor (10), svalů ruky (11,12,13), popřípadě s jiným obsahemkalciumfosfát a kalciumpyrofosfát (14). Pro klinickou praxi nejvýznamnější je však jednoznačně precipitace kalciumhydroxyapatitu v rotátorech ramenního kloubu.…”
unclassified